Auditoría de gestión y su relación con la optimizaciónde los servicios del colegio de bachillerato técnico Rafael Vásconez Gómez de cantón La Maná, año 2012. - Millingalli Pumacuro, Myrian Yolanda (2015)
The present research is to analyze the impact of the application of an audit of management regarding optimization services Technical College Baccalaureate Vásconez Rafael Gómez order to assess the level of trust in financial reporting , in addition to examining the involvement in the planning of resources and analyze the performance of the legal basis the audit process was performed by the following steps prior foundation for the development of the same activities , the first phase is the preliminary report of knowledge where the diagnosis is made situational company , the second phase consists of planning file , in reviewing the internal control departments of the company organizing the third phase is the implementation and analysis is where the functions of each department is made and Finally the respective reports to the authorities of the school, took the non-experimental design since documents related to the analysis of management by each department were noted. In non- experimental research independent variables have already occurred and can not be manipulated , the researcher has no direct control over these variables can not affect them because they happened , like their effects , for the proper analysis of the results applied the IFRS for SMEs allows us to guarantee the veracity of the information to obtain an acceptable degree of confidence in the application of the same so it is important to perform an analysis of the management setting.